Total Synthesis of (-)-Decarbamoyloxysaxitoxin - Iwamoto, Osamu; Koshino, Hiroyuki; Hashizume, Daisuke; Nagasawa, Kazuo (Angewandte Chemie (International ed.), 2007)
A facile and general synthetic strategy for saxitoxin derivatives has been developed, as exemplified by the efficient synthesis of (−)‐decarbamoyloxysaxitoxin ((−)‐doSTX), the putative enantiomer of the natural product, in 17 steps and in 10 % overall yield. The synthesis features a diastereoselective 1,3‐dipolar cycloaddition and a direct oxidation with o‐iodoxybenzoic acid (IBX; see scheme, Cbz=benzyloxycarbonyl).